The Backgrounds of the American Political Identity - Mihoubi, Houria (Journal of Legal Studies and Researches, 2021)
The topic of the present research paper revolves around The Backgrounds of the American Political Identity .The paper focuses on The Backgrounds of the American political thought, which is the cornerstone of all the social transformations and developments that the American society has known throughout the modern history of the United States of America. In the end, the research concludes that the American political thought was the result of the great impact of history, religion, and European philosophy on the Founding Fathers.